2022
DOI: 10.1111/jsr.13611
|View full text |Cite
|
Sign up to set email alerts
|

Daily and average associations of physical activity, social media use, and sleep among adolescent girls during the COVID‐19 pandemic

Abstract: Summary Adolescents’ daily lives have been disrupted during the Coronavirus disease 2019 (COVID‐19) pandemic. It remains unclear how changes in adolescents’ daily physical and social behaviours affect their sleep. The present study examined the daily and average effects of physical activity and social media use (i.e., video chatting, texting, and social networking sites) on adolescent girls’ sleep during the COVID‐19 pandemic. Adolescent girls aged 12–17 years ( N = 93; 69% Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…Recent studies show that the nationwide lockdowns and closure of schools during the pandemic may cause increased the frequency of internet addiction (Chen, Chen, Pakpour, Griffiths, & Lin, 2020 ; Fegert, Vitiello, Plener, & Clemens, 2020 ). Further, a recent study indicates that physical activity and social media use may affect later adolescent sleep timing during the COVID‐19 pandemic (Hamilton, Hutchinson, Evankovich, & Ladouceur, 2022 ). Similar to these studies, we found that the rate of both problematic internet use and poor sleep quality was higher in adolescents, who were unable to continue their hobbies and physical activities because of restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the nationwide lockdowns and closure of schools during the pandemic may cause increased the frequency of internet addiction (Chen, Chen, Pakpour, Griffiths, & Lin, 2020 ; Fegert, Vitiello, Plener, & Clemens, 2020 ). Further, a recent study indicates that physical activity and social media use may affect later adolescent sleep timing during the COVID‐19 pandemic (Hamilton, Hutchinson, Evankovich, & Ladouceur, 2022 ). Similar to these studies, we found that the rate of both problematic internet use and poor sleep quality was higher in adolescents, who were unable to continue their hobbies and physical activities because of restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7 studies measured both sleep and mental health outcomes [ 31 , 45 •, 46 48 , 50 , 59 ]. Five of these studies reported significant associations among SMU, sleep, and mental health outcome [ 31 , 45 •, 46 , 50 , 59 ].…”
Section: Synthesis Of Recent Findingsmentioning
confidence: 99%
“…A total of 7 studies measured both sleep and mental health outcomes [ 31 , 45 •, 46 48 , 50 , 59 ]. Five of these studies reported significant associations among SMU, sleep, and mental health outcome [ 31 , 45 •, 46 , 50 , 59 ]. It was reported that SMU was significantly associated with poor sleep quality and increased mental health issues [ 31 , 45 •, 46 , 50 , 59 ], and sleep was found to mediate the negative impacts of SMU on mental health and emotional symptoms in adolescents [ 45 •].…”
Section: Synthesis Of Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, sleep problems in adolescents during the pandemic have also been frequently associated with specific daily habits. Specifically, longer screen time [ 135 , 136 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ] and lower physical activity [ 149 , 154 ] have been associated with different measures of poor sleep quality. Considering the influence of these variables on sleep habits in adolescents [ 14 , 155 , 156 , 157 ], these findings are consistent with the increased screen time and sedentary behaviors observed in youth during the pandemic [ 119 , 120 , 121 , 122 , 141 ].…”
Section: The Impact Of Covid-19 Outbreak On Sleep and Mental Health I...mentioning
confidence: 99%